(p-5)^2 = p^2 - 25 NOT p^2+25 .

(3+p)^2 ≠ 9+p^2and(p-5)^2 ≠ p^2 +25

Im not really to sure, as i am in the opinion that (-5)^2 is still 25

(p-5)^2 is NOT EQUAL TO (p^2 + 25) (p-5)^2 = (p-5)(p-5) = (p^2-5p-5p+25) = (p^2-10p+25)So..... this is w®øng

(p-5)^2 = p^2 - 25 (p-5)^2 ≠ p^2 + 25

when (3+p)^2 is expanded it is (3+p)(3+p) which is 9 + 6p + p^2. and for (p-5)^2 when expanded is (p-5)(p-5) which is p^2 -10p + 25

(p-5)^2 ≠ (p^2 + 25) (p-5)^2 = (p-5)(p-5)= (p^2-5p-5p+25)= (p^2-10p+25)Therefore this is wrong. Hey mark, same answer :D

We're not doing single terms only...so don't change the sign

we cannot just power the expression up directly. (p-5)^2 = p^2 -25NOT p^2 +25

(p-5)^2 ≠p+25(p-5)^2= (p+5)(p+5)

(p-5)^2 does not equal p+25. it should equal to (p+5)(p+5)

(p-5)^2 = p^2 - 25 NOT p^2+25 .

ReplyDelete(3+p)^2 ≠ 9+p^2

ReplyDeleteand

(p-5)^2 ≠ p^2 +25

Im not really to sure, as i am in the opinion that (-5)^2 is still 25

ReplyDelete(p-5)^2 is NOT EQUAL TO (p^2 + 25)

ReplyDelete(p-5)^2 = (p-5)(p-5)

= (p^2-5p-5p+25)

= (p^2-10p+25)

So..... this is w®øng

(p-5)^2 = p^2 - 25

ReplyDelete(p-5)^2 ≠ p^2 + 25

when (3+p)^2 is expanded it is (3+p)(3+p) which is 9 + 6p + p^2. and for (p-5)^2 when expanded is (p-5)(p-5) which is p^2 -10p + 25

ReplyDelete(p-5)^2 ≠ (p^2 + 25)

ReplyDelete(p-5)^2 = (p-5)(p-5)

= (p^2-5p-5p+25)

= (p^2-10p+25)

Therefore this is wrong. Hey mark, same answer :D

We're not doing single terms only...so don't change the sign

ReplyDeletewe cannot just power the expression up directly.

ReplyDelete(p-5)^2 = p^2 -25

NOT p^2 +25

(p-5)^2 ≠p+25

ReplyDelete(p-5)^2= (p+5)(p+5)

(p-5)^2 does not equal p+25. it should equal to (p+5)(p+5)

ReplyDelete